The lucky country? Life satisfaction in Australia 2001-2010 - Ambrey, C; Fleming, C. M. (Griffith University, 2012)
Employing data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, this paper examines the level, determinants and distribution of self-reported life satisfaction, as well as the prevalence and severity of dissatisfaction in Australia over the period 2001-2010. Against most objective measures, Australia’s economic performance during this period was exemplary. Yet our results indicate an overall downward trend in life satisfaction, as well as a diminishing gap between the life satisfaction of males and females. Geographic heterogeneity in the distribution of life satisfaction is apparent, and a number of socio-economic and demographic factors are found to serve an important role in determining an individual’s level of life satisfaction. Results also suggest that inequality in life satisfaction has generally declined. Measures of the extent of dissatisfaction reveal an encouraging downward trend and provide policy makers with an alternative perspective from which to assess societal welfare.
Discussion Papers Economics
Keywords: Life Events; Satisfaction -- Life; Disadvantage, adversity and resilience; Satisfaction; Life Events; Life; Dsiadvantage, adversity and resilience; Adversity and resilience